Revisión documental de los factores que influyen en la reinserción social y laboral positiva de los reclusos de las cárceles de Colombia - Gutiérrez Jiménez, Karla Patricia (Universidad Antonio Nariño, 2021)
The objective of this research is to document and identify the variables that position the positive social reintegration of inmates in Colombian prisons, in this way some authors define the social reinsertion of people who break the law as one of the central objectives of the programs intervention in prisons in Chile (Gendarmería de Chile, 2008). The term of social reintegration has different meanings linked to who uses it and the public to whom it is directed (Fundación Tierra de Esperanza, 2013). This diversity gives it an ambiguous character that hinders its practical operationalization (Pérez, 2009). This concept has at least three perspectives related to the normative, institutional and theoretical (Villagrán, 2008). For the present documentary review, the documentary method was used, whose primary objective is to choose and select the information by reviewing documents, books and magazines. Reason that gave merit to an extensive review of the literature and a background search was carried out regarding the issue in the mansion, direct information from some prisons, among others. Taking this review into account, an analysis of each of the acquired documents was carried out. Based on the above, it can be concluded that the problem of social reintegration of inmates in prisons in Colombia has several psychosocial factors that require analysis as soon as possible, in order to guarantee that the ex-inmate can rebuild his social and working life.